Áreas subutilizadas na Ilhinha, São Luís-Maranhão: a requalificação por meio da Permacultura, como alternativa de sustentabilidade ambiental - COSTA, Ariana Kelly Martins (2022)
The appropriation of urban spaces has been an alternative for their sustainable use, a condition reiterated in the capital of Maranhão. The presente research aims to analyze the relevance of requalifying areas of the Ilhinha, in São Luís-Maranhão, through Permaculture, considering social coexistence, income generation and quality of life, as an alternative for sustainability. The research evokes the memory and the socio-spatial of the community about its organization, focusing on the relevance of the requalification of areas in social dysfunction, through Permaculture. The methodology comprises documentary and field research, adopting as procedures: analysis of the literature on the object of study, photographic record and information on the construction of history, and participant observation of the residents' socio-spatial experience. Due to the Coronavirus pandemic, the research was carried out in a hybrid way, through semi- structured interviews with community leaders, as well as former residents who were part of the construction of the history and memory of the area, who are aware of the socio-spatial dynamics and realization of field visit when necessary. The results show the need to expand green areas and leisure spaces. There was no feeling of belonging of the community of Ilhinha by the street it occupies, as well as disappointment of the community, due to the shortcomings pointed out in this work.